2017
DOI: 10.1086/694319
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Diversification and Time Explain Amphibian Richness at Different Scales in the Tropical Andes, Earth’s Most Biodiverse Hotspot

Abstract: The Tropical Andes make up Earth's most species-rich biodiversity hotspot for both animals and plants. Nevertheless, the ecological and evolutionary processes underlying this extraordinary richness remain uncertain. Here, we examine the processes that generate high richness in the Tropical Andes relative to other regions in South America and across different elevations within the Andes, using frogs as a model system. We combine distributional data, a newly generated time-calibrated phylogeny for 2,318 frog spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
83
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 96 publications
10
83
2
3
Order By: Relevance
“…We have observed results suggesting this pattern in our own analyses (Hutter et al. ). Given this, studies that have found negative results using BAMM (e.g., nonsignificant relationships) should be viewed with particular caution.…”
Section: Bamm Versus the Ms Estimatorssupporting
confidence: 73%
“…We have observed results suggesting this pattern in our own analyses (Hutter et al. ). Given this, studies that have found negative results using BAMM (e.g., nonsignificant relationships) should be viewed with particular caution.…”
Section: Bamm Versus the Ms Estimatorssupporting
confidence: 73%
“…Thus, geographic scale and isolation likely influence the mechanism by which diversification occurs, as has been suggested in the tropical Andes (Hutter et al. ). Despite the limited space afforded to colonists of Luzon compared to continental radiations, the patterns of LOE diversification were more consistent with a mechanism of allopatric speciation, where species diversity is able to accumulate nearly constantly, offset slightly by background extinction rates.…”
Section: Discussionmentioning
confidence: 89%
“…Jansson & Davies, ; Pyron & Wiens, ; Rolland, Condamine, Jiguet, & Morlon, ), especially high‐elevation tropical habitats (e.g. Hughes & Eastwood, ; Hutter, Guayasamin, & Wiens, ; Hutter et al, ). However, in our results (Table ), the best‐fitting model to explain variation in diversification rates includes violet colour alone.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that certain fruit colours may be favoured in environments that promote rapid diversification (e.g. montane tropical regions; Hughes & Eastwood, ; Hutter, Lambert, & Wiens, ; Spriggs et al, ). Thus, fruit colour itself may not directly drive diversification, but there might be a synergy between fruit colour and geographic distribution that affects diversification.…”
Section: Introductionmentioning
confidence: 95%